EFFICACY OF PANBIOTM COVID-19 AG RAPID TEST IN SARS-COV-2 DETECTION: COMPARISON WITH RT-PCR TEST - Shabana Asif,; Aashi Ahmed,; Gul, Ambreen; Tariq Abbasi, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Evidence on performance of Rapid Antigen Detection Tests to recognize SARS-CoV-2 symptomatic patients in our context is limited. This study was aimed to evaluate Panbio„¢ COVID-19 Ag Rapid Test Device (Abbott Diagnostics, Jena, Germany) in identifying SARS-CoV-2 infection in comparison with RT-PCR test. Methods: This cross-sectional validation study was carried out at Margalla Hospital, Taxila from October, 2020 to March, 2021. Three hundred and eighty-two participants of both gender and all ages, symptomatic for 3-4 days were included in this study. For each participant, two nasopharyngeal swabs were collected by trained lab technicians according to SOPs, one for Rapid Antigen Test and other for RT-PCR.Covid-19 antibodies were checked 4-6 weeks after symptoms among 77 randomly selected participants to further evaluate the performance of Rapid Antigen Test. Data was analyzed using SPSS-26. Results: The mean age of the participants was 43.1 years (SD= 15.9). More than half of participants were males (n=213%=55.8) and 169 (44.2%) were females. Sensitivity of Rapid Antigen Test was calculated to be 94.3%, whereas the specificity was 39.7%. Out of 34 RT-PCR negatives that were initially detected positive on Rapid Antigen Test, 33 demonstrated presence of COVID-19 antibodies. Conclusion: Panbio„¢ COVID-19 Ag Rapid Test was found to have 93.4% overall sensitivity and relatively low overall specificity (37.9%). Rapid antigen testing using Panbio„¢ COVID-19 Ag Rapid Test Device can be effectively used to scale up mass testing to interrupt transmissibility of COVID-19 infection by generating quick result.